2016
DOI: 10.1177/1059601116664610
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Employees’ Perceptions of Green HRM and Non-Green Employee Work Outcomes: The Social Identity and Stakeholder Perspectives

Abstract: Green human resource management (green HRM) refers to a set of HRM practices that organizations adopt to improve employee workplace green performance. While the effect of perceived green HRM on employee workplace green performance has received some empirical support, its relationship with employee non-green workplace outcomes remains unexplored and, therefore, unknown. This research tests an integrative moderated-mediation model related to the relationship between perceived green HRM and non-green workplace ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
301
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(319 citation statements)
references
References 80 publications
11
301
4
3
Order By: Relevance
“…The literature suggests that the relationship between GHRM and employee green behaviors is not universal and may fluctuate depending on individual and organizational characteristics. For instance, Shen et al () empirically confirmed that the relationship of GHRM with non‐green employee performance and behavioral intentions was moderated by perceived organizational support. Further, Dumont et al () established employee green values as moderator of GHRM–employee green behaviors relationship.…”
Section: Theoretical Framework and Research Propositionsmentioning
confidence: 98%
See 1 more Smart Citation
“…The literature suggests that the relationship between GHRM and employee green behaviors is not universal and may fluctuate depending on individual and organizational characteristics. For instance, Shen et al () empirically confirmed that the relationship of GHRM with non‐green employee performance and behavioral intentions was moderated by perceived organizational support. Further, Dumont et al () established employee green values as moderator of GHRM–employee green behaviors relationship.…”
Section: Theoretical Framework and Research Propositionsmentioning
confidence: 98%
“…However, further research is encouraged to confirm the above findings.This study makes several important contributions to the literature.First, by investigating the effect of GHRM practices on employee taskrelated and voluntary green behaviors, it adds to the scarce literature that links GHRM with employee workplace behaviors. Most of the studies have considered either the effect of general HRM practices on employee green performance behaviors(Paillé, Chen, Boiral, & Jin, 2014) or GHRM practices on employee general performance behaviors(Shen et al, 2018). Second, it establishes organizational identification as the essential socio-psychological process via which GHRM exercises its influence on employee green performance behav-iors.…”
mentioning
confidence: 99%
“…Therefore, company starts to implement the environmental management system for its sustainable existence. In fact, this implementation has not gone as expected, some researchers then proceed to further examine the causes of detrimental factors in implementing the environmentally management system, starting from planning aspect, organizing aspect, until controlling aspect [13,22].…”
mentioning
confidence: 99%
“…Green HRM is a new concept related to the employee management involving HRM practices with eco-friendly principle. The implementation of Green HRM is not only required in the business world, but also in the education world, especially at university as a source of knowledge to shape green behavior of its members [4,5,22]. This study is considered pivotal for some reasons.…”
mentioning
confidence: 99%
“…These functions highlight the necessity of some green initiatives like green building, paperless office, energy conservation, recycling and waste disposal, etc. [21].All these functions and green initiatives of HRM consequently embody some strategies to motivate or enforce employees to behave green and become involved in environmentallyfriendly activities [22][23] [24]. One potential alternative is to let the benefits of employees be affected by the costs that can be avoided through cost-saving behaviors within organizations.…”
Section: Green Businesses and Green Human Resource Managementmentioning
confidence: 99%